Constitutional rights of the child: definition and meaning for the children’s rights institution - Bakalo, Liliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The Constitution of Ukraine does not contain special provisions dedicated children's rights. Therefore, as a general rule, the constitutional rights of children in Ukraine are considered in the context of fundamental human rights, taking into account the dependence of the scope of rights on the age of the person. As a consequence of such uncertainty, the preconditions for the violation of the rights of minors remain in the state. One of the reasons for this situation - the lack of attention of legislators and the scientific community to the importance of the institution of constitutional rights of the child in Ukraine developing.The article explores and analyzes the scientific approaches of domestic and foreign legal scholars, as well as children's human rights defenders views to the interpretation of the concept of "constitutional rights of the child" and to the justification of the importance of this institution.The study revealed the disadvantages of the existing definitions of the concept, as well as highlighted the specific features inherent only in the constitutional rights of children. At the same time, the article analyzes the opinions of foreign lawyers regarding the importance of enshrining in the selected Constitutions of the countries of special articles on the rights of children, separated from the general fundamental human rights.It has been established that the “constitutional rights of children” have a much extensive interpretation, which includes not only basic natural human rights, but also trusted civil and special rights. In addition, the study substantiates the importance of separating the rights of children from the main provisions on human rights in the Constitution of Ukraine.As a result of the study, an own approach to understanding the concept of «children’s constitutional rights» has been developed and the conclusion is substantiated that there is a negative impact on ensuring the rights of small citizens due to the lack of their constitutional separation from the rights of adults